Applying the Economic Model of Crime to Child Support Enforcement: A Theoretical and Empirical Analysis - Beron, Kurt J. (The Review of Economics and Statistics, 1988)
Child support noncompliance affects both the family and the taxpayer. This papers models the decision to pay based on expected utility maximization. The amount unpaid is determined jointly with the expected enforcement probability. A two-stage estimation technique requiring ordinary least squares and probit is used. The author improves upon previous problems with measurement error and sex-restricted data in deterrence and child support studies, the treatment of endogenous deterrence variables as exogenous, and the use of aggregate data. He finds a joint relationship between the amount unpaid and the enforcement probability. Policies are suggested for increasing compliance and payments to the family. Copyright 1988 by MIT Press.